Supervisory objectives, practices and teachiques in the elementary schools of the province of Romblon - Platon, Lauro S. 1912- (s.n.], 1965)
This study determines the objectives of the supervisors in their supervision of elementary schools and the practices and techniques they employ in supervision. It aims at the improvement of supervision in the elementary schools in the division.